Jevons Paradox: Sustainable Development Goals and Energy Rebound in Complex Economic Systems - Louise Ellegaard Fich; Silvia Viola; Niclas Scott Bentsen (Energies, 2022)
Jevons Paradox has fundamental implications on sustainable development and the UN Sustainable Development Goals (SDGs). The paradox states that technological improvements aiming to increase the energy efficiency risk causing a rebound effect, and an increase in demand, production, and resource exploitation. Third world countries undergoing early-stage technological development may be particularly vulnerable, but it is also relevant in complex economic systems, where policymaking on climate and energy building on insufficient knowledge and attention to rebound effects can impair the desired outcome in terms of climate change mitigation, resource use and sustainable development.